Higher self‐reported severity of atopic dermatitis in adults is associated with poorer self‐reported health‐related quality of life in France, Germany, the U.K. and the U.S.A. (28th October 2019) - Andersen, L.; Nyeland, M.E.; Nyberg, F.
Summary: Background: Better understanding of the relationship between atopic dermatitis (AD) severity and health‐related quality of life (HRQoL) could help improve knowledge of a more effective treatment for people with AD. Objectives: To assess the relationship between AD severity and HRQoL and perception of AD symptoms in adults with moderate‐to‐severe AD in Europe and the U.S.A. Methods: Participants for this cross‐sectional, internet‐based survey were recruited from the larger population‐based National Health and Wellness Survey. AD severity was measured by Patient‐Oriented SCORing of AD. HRQoL was measured by the five‐level EuroQol‐5D, Dermatology Life Quality Index (DLQI) and Patient‐Oriented Eczema Measure (POEM). Results: Altogether, 1232 respondents were included: 1098 (89·1%) with moderate‐to‐severe AD [221 (20·1%) from France, 209 (19·0%) from Germany, 118 (10·7%) from the U.K. and 550 (50·1%) from the U.S.A.]. An additional 134 (10·9%) respondents with mild AD were included. Sociodemographic and clinical AD characteristics were similar between countries. In adults with moderate‐to‐severe AD, higher AD severity correlated with poorer HRQoL (Spearman's r = –0·38 and 0·61 for EQ‐5D and DLQI, respectively; both P < 0·001). AD severity was positively correlated with POEM (Spearman's r = 0·51; P < 0·001). People with moderate‐to‐severe vs. those with mild AD had poorer health outcomes (EQ‐5D, DLQI and POEM, P < 0·001 for all). These results were similar and consistent for the European and the U.S. populations separately. Conclusions: Higher AD severity is associated with poorer HRQoL across Europe and the U.S.A. This is a burden for patients and may provide encouragement for more effective management of AD. What's already known about this topic? Atopic dermatitis (AD) is associated with a detrimental effect on health‐related quality of life (HRQoL), including sleep disturbance, anxiety and depression. Limited data describing the relationship between different levels of AD severity and self‐reported HRQoL have been published. What does this study add? There is a positive association between increasing AD severity (Patient‐Oriented SCORing of AD) and decreasing HRQoL (EQ‐5D and Dermatology Life Quality Index) and the perception of AD symptoms (Patient‐Oriented Eczema Measure) from the patient's perspective. AD severity according to geographic locations was explored (France, Germany, the U.K., and the U.S.A.), showing that the decreasing HRQoL associated with increasing AD severity was quite consistent between the geographic locations. What are the clinical implications of this work? The results of this study showed that higher AD severity is associated with poorer HRQoL from the subject's perspective in both Europe and the US. This fact confirms that there is a burden for these patients and may provide encouragement for a more effective management of AD, especially among those with greater AD severity. Abstract : Linked Comment: Rencz. Br J Dermatol 2020; 182:1083 .